What the psychiatrist needs to know about the coroner's court in England and Wales. (May 2022) - van Dellen, Anton; Harris, Andrew; Merryweather, James; Simsek, Ceylan; Pendlebury, Gabrielle
SUMMARY: It is highly likely that a psychiatrist will be called to an inquest at some point in their career. Our aim in this article is to educate psychiatrists in relation to the law and processes of a coroner's court in England and Wales and provide guidance on engaging with the system. To achieve this we review and discuss the relevant law and medico-legal aspects of inquests. Knowledge and preparation are key to negotiating any inquest and we would hope that the understanding and guidance offered in this article will reduce anxiety, make the situation manageable and aid professionalism, in often tragic circumstances.